A comparative ethnoarchaeological analysis of corporate territorial ownership. (February 2015) - Freeman, Jacob; Anderies, John M.
Abstract: Ecological models are a fundamental tool that archaeologists use to clarify our thinking about the processes that generate the archaeological record. Typically, arguments reasoned from a single model are bolstered by observing the consistency of ethnographic data with the argument. This validation of a model establishes that an argument is reasonable. In this paper, we attempt to move beyond validation by comparing the consistency of two arguments reasoned from different models that might explain corporate territorial ownership in a large ethnographic data set. Our results suggest that social dilemmas are an under appreciated mechanism that can drive the evolution of corporate territorial ownership. When social dilemmas emerge, the costs associated with provisioning the public goods of information on resources or, perhaps, common defence create situations in which human foragers gain more by cooperating to recognize corporate ownership rules than they lose. Our results also indicate that societies who share a common cultural history are more likely to recognize corporate ownership, and there is a spatial dynamic in which societies who live near each other are more likely to recognize corporate ownership as the number of near-by groups who recognize ownership increases. Our results have important implications for investigating the coevolution of territorial ownership and the adoption of food production in the archaeological record. Highlights: We develop an approach that compares arguments reasoned from two different ecological models. We investigate the socioecology of corporate territorial ownership with a large sample of ethnographic cases. Social dilemmas are an under-appreciated mechanism that drives the evolution of corporate territorial ownership. Cultural transmission plays a role in the evolution of corporate ownership. New models that incorporate both ecological dynamics and transmission processes are needed.